Elevated Serum Alpha-Fetoprotein Is a Significant Prognostic Factor for Patients with Gastric Cancer: Results Based on a Large-Scale Retrospective Study - Zhan, Zhouwei; Chen, Bijuan; Yu, Jiami; Zheng, Jingxian; Zeng, Yi; Sun, Mingyao; Peng, Li; Guo, Zengqing; Wang, Xiaojie (Frontiers in Oncology, 2022)
Objectives The aim of this work is to study the clinicopathological features and prognostic factors of serum alpha-fetoprotein (AFP)–positive gastric cancer (GC). Methods A cohort study including 2,318 patients with GC who underwent radical surgery from January 2008 to December 2015 was retrospectively analyzed. Patients were divided into two groups according to preoperative serum AFP values: 191 patients with AFP-positive GC (AFP > 20 ng/ml, 8.24%) and 2,127 patients with AFP-negative GC (AFP ≤ 20 ng/ml, 91.76%). The clinicopathological features and prognostic factors were explored. Results Compared with AFP-negative GC, AFP-positive GC had higher rates of liver metastasis, lymph node metastasis, venous invasion, and nerve invasion (all P < 0.05). The 5-year OS, DFS, and mLMFS of AFP-positive GC were shorter than AFP-negative GC (55.00% vs. 45.04%, P < 0.001; 39.79% vs. 34.03%, P < 0.001; 13.80 months vs. 16.25 months, P = 0.002). In whole cohort, multivariate analysis found that serum AFP levels (positive vs. negative), pT stage, pN stage, nerve invasion (yes or no), and venous invasion (yes or no) were independent prognostic factors. Serum AFP levels (20–300 ng/ml vs. 300–1,000 ng/ml vs. >1,000 ng/ml), pT stage, pN stage, and venous invasion (yes or no) were independent prognostic factors in AFP-positive GC. Conclusion Liver metastases and venous invasion are more likely to occur in AFP-positive GC and lead to poor prognosis. Serum AFP level is an independent prognostic factor in patients with GC. As the level of AFP increases, the prognosis becomes worse.